How do block training and circuit training affect physical fitness? A comparative study of futsal athletes - Sabransyah, Mohammad; Asmutiar; Rajidin; Sari, Suriani; Rubiyatno (UIR Press, 2025)
Background: Physical fitness is a fundamental component of performance in futsal, a sport that demands high levels of stamina, strength, and endurance. Despite the abundance of training programs available, few have been systematically tested for their effectiveness in enhancing fitness among futsal athletes. Research Objectives: This study aims to compare the effectiveness of block training and circuit training in improving physical fitness among male futsal athletes. Methods: A quasi-experimental design with a two-group pretest-posttest structure was employed. Twenty male futsal athletes from Universitas PGRI Pontianak were selected through purposive sampling and divided equally into a block training group and a circuit training group. Both groups underwent 12 training sessions over four weeks, each performed at full intensity (100% 1RM) using 10 fitness stations, including leg press, bench press, and sit-ups. Physical fitness was assessed using the Cooper test. Data were analyzed using paired and independent t-tests, with normality confirmed through the Shapiro-Wilk test. Finding/Results: Both training methods significantly improved the athletes’ physical fitness levels (p < 0.05). Although circuit training yielded slightly better average improvements than block training, the difference between the two was not statistically significant (p = 0.385). Conclusion: Both block and circuit training are effective in enhancing the physical fitness of futsal athletes. While circuit training may offer slight advantages in practical implementation, the absence of a statistically significant difference suggests that both methods can be applied flexibly based on training goals and athlete preferences. Future research should explore comparisons with other conditioning methods, such as high-intensity interval training (HIIT) or plyometrics, to identify the most optimal training strategy.